Enhancing Student Assessment and Well-Being Through School–Community Engagement in Vocational Boarding Education - Estin Indria Maahury; Listen Henty Telussa; Salma Marasabesy; Sulva Patty; Susan Sunset; Rastika Tepinalan (DEVOTIONIS, 2025)
This study explores how school–community engagement can enhance student assessment skills and overall well-being within the context of vocational boarding education. Conducted at SMK Pertanian Pembangunan Ambon, a vocational high school specializing in agriculture in Eastern Indonesia, the project aimed to support guidance and counseling teachers in identifying students’ developmental challenges and to improve students’ abilities in using assessment tools. Using a qualitative descriptive method, data were collected through observation, interviews, and document analysis involving dormitory managers and school leadership. Findings revealed that the boarding system plays a pivotal role in promoting academic success, especially for students from remote areas, by providing a structured and supportive environment. Key services included structured mentoring, extracurricular activities, and a well-organized dormitory management structure. The assessment phase identified a variety of student issues: personal problems (42.6%), academic difficulties (34%), social issues (12.7%), and career uncertainty (10.7%). These findings highlight the urgent need for a responsive, student-centered counseling system supported by the school and local community. The study recommends targeted improvements in dormitory infrastructure, professional development for staff, and stronger integration of assessment-driven decision-making. Overall, the project demonstrates that a well-managed residential education model, when coupled with active community engagement, can significantly foster student well-being, guidance responsiveness, and life skill development.